2010
DOI: 10.1016/j.ijrobp.2009.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Improved Intratumoral Oxygenation Through Vascular Normalization Increases Glioma Sensitivity to Ionizing Radiation

Abstract: Purpose Ionizing radiation, an important component of glioma therapy, is critically dependent on tumor oxygenation. However, gliomas are notable for areas of necrosis and hypoxia, which foster radioresistance. We hypothesized that pharmacologic manipulation of the typically dysfunctional tumor vasculature would improve intratumoral oxygenation and, therefore, the anti-glioma efficacy of ionizing radiation. Methods and Materials Orthotopic U87 xenografts were treated with either continuous interferon-beta (IF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
87
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(91 citation statements)
references
References 37 publications
2
87
0
2
Order By: Relevance
“…Dings and colleagues showed that radiotherapy was most effective when administered after treatment with bevacizumab in ovarian, breast, and melanoma models (25). Bevacizumab and continuous delivery of IFN-b presented changes consistent with normalization and increased radiation response in an orthotopic glioma model (26).…”
Section: Discussionmentioning
confidence: 99%
“…Dings and colleagues showed that radiotherapy was most effective when administered after treatment with bevacizumab in ovarian, breast, and melanoma models (25). Bevacizumab and continuous delivery of IFN-b presented changes consistent with normalization and increased radiation response in an orthotopic glioma model (26).…”
Section: Discussionmentioning
confidence: 99%
“…As discussed below, many studies testing the effects of antiangiogenic drugs have shown a presence of a "normalization window"-a time period beginning with the appearance of a normalized vascular phenotype (typically within 1 -2 days of starting treatment), and ending when features of normalization are lost Winkler et al 2004;Jain 2005b;Batchelor et al 2007;Kamoun et al 2009 Xian et al 2006;McCarty et al 2007;Mazzone et al 2009. c This is controversial given recent reports of increased metastasis after antiangiogenic therapy in certain animal models (Ebos et al 2009;Paez-Ribes et al 2009 Gorski et al 1999;Hansen-Algenstaedt et al 2000;Lee et al 2000;Kozin et al 2001;Ader et al 2003;Winkler et al 2004;Ansiaux et al 2005Ansiaux et al , 2006Pore et al 2006a;Dings et al 2007;Kashiwagi et al 2008;Batra et al 2009;Cerniglia et al 2009;Tsukada et al 2009;McGee et al 2010. g Teicher et al 1995a,b;Wildiers et al 2003;Segers et al 2006;Dickson et al 2007a,b,c;Bhattacharya et al 2008Bhattacharya et al , 2009Zhou et al 2008;Juan et al 2009;Zhou and Gallo 2009;J Liu, S Liao, B Diop-Frimpong, et al, unpubl. data. section, we discuss the key molecules implicated in tumor vessel biology with a focus on their role in regulating vascular normalization.…”
Section: Evidence For Vascular Normalization In Tumors Preclinical Evmentioning
confidence: 99%
“…d Inai et al 2004;Tong et al 2004;Nakahara et al 2006;Dickson et al 2007b;Dings et al 2007;Fischer et al 2007;Zhou et al 2008;Falcon et al 2009;Juan et al 2009;Kamoun et al 2009;Ohta et al 2009;Zhou and Gallo 2009;Chae et al 2010;Primo et al 2010. Lee et al 2000;Winkler et al 2004;Dings et al 2007;Fischer et al 2007;Eichhorn et al 2008;Batra et al 2009;Skuli et al 2009;McGee et al 2010. j Teicher et al 1995bJain et al 1998;Bernsen et al 1999;Cohen-Jonathan et al 2001;Delmas et al 2003;Ansiaux et al 2005Ansiaux et al , 2006Pore et al 2006b;Segers et al 2006;Cerniglia et al 2009;Qayum et al 2009;Cham et al 2010. k Ader et al 2003;Hamzah et al 2008;Kashiwagi et al 2008;Stockmann et al 2008;Maione et al 2009;Mazzone et al 2009;Skuli et al 2009;Tsukada et al 2009;Rolny et al 2011…”
Section: Vegfunclassified
“…7 The inhibitors of VEGF in the therapy of central nervous system malignancy normalizes tumor vasculature and decrease tumor interstitial pressure, leading to an improved access of cytoreductive drugs and radiotherapy efficacy, due to an increased oxygen delivery [39]. However, these agents may also restore the low permability characteristics of normal brain microvasculature, counteracting beneficial effects.…”
Section: The Controversial Effect Of Vascular Normalization In the Trmentioning
confidence: 99%